Emotional labor, job satisfaction, and retention among home care workers in Taiwan: a comprehensive analysis - Kuo, Tung-Sheng; Chu, Li-Chuan; Shih, Chia-Lung; Li, Ya-Ching; Kao, Pi-Lien (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the relationships between emotional labor, job satisfaction, and retention among home care workers in Taiwan.Materials and methodsThis study is a cross-sectional study design. Data were randomly collected from home care workers in Taiwan’s Chiayi region through questionnaires. We included 365 participants, primarily female (80.3%), with ages ranging from 18 to 60 years old. The questionnaires assessed emotional labor, job satisfaction, and retention intention. Data analysis was conducted using IBM SPSS Statistics software (version 28.0) and included descriptive statistics, factor analysis, reliability analysis, t-tests, one-way ANOVA, Pearson correlation coefficients, K-means cluster analysis, and path analysis.ResultsThe study included 365 participants, with females comprising the majority (80.3%). Emotional labor exhibits a significant positive relationship with job satisfaction (β = 0.157, p < 0.01) and willingness to stay (β = 0.115, p < 0.05). However, job satisfaction shows no significant relationship with willingness to stay (β = 0.48, p > 0.05). The participants were arbitrarily classified into two clusters based on cluster analysis. Cluster 1 exhibited more genuine emotional expressions (deep acting) during work, demonstrated higher job satisfaction, and showed a greater willingness to stay.ConclusionThe study provides insights into the relationships between emotional labor, job satisfaction, and retention among home care workers in Taiwan. The findings aim to offer valuable insights for managers in hospitals and long-term care facilities to enhance their recruitment strategies and personnel management practices.